Fast Food Simulacra: How MSMEs in Surakarta City Strategize Digitalization In Generation Z Consumption Patterns - Arya Danendra Kurnia Dipraja; Diah Puspaningrum; Desita Wahyu Ningrum; Adnandya Muhammad Triwardana; Alief Putri Margiutami; Afifah Melani Putri; Bintang Fahreza; Arientyara Noegraheni; Erie Irawan Heryanto; Effieta Alfi Wulandari (Tourism Department, State Polytechnic of Banyuwangi, 2025)
Globalization drives digitalization in many economic sectors, including businesses; which influence fast food Micro, Small, and Medium Enterprises (MSMEs). The purpose of this research is to analyze the strategies these MSMEs develop, which includes analyzing supporting and inhibiting factor, as a response of Gen-Z changes in consumption pattern. This research uses qualitative method and social fact paradigm to describe how MSMEs adapt to technological developments. The result shows that in response of changes in consumption pattern, MSMEs subjects executing some strategies to support their enterprise in digital era, using food delivery services, social media marketing, and digital training. The lack of technology literacy and human resources becomes the inhibiting factors since enterprises are managed independently by the owner, making digital promotion difficult. This research contributes to society, especially to fast food entrepreneurs in terms of understanding digital businesses. The input of this research also contributes for government to strengthen collaboration between digital platform and also provides relevant training to support MSMEs transformation in digital era.